Molecular characterization of cubios (Tropaeolum tuberosum Ruíz and Pavón) in the department of Boyacá - Morillo C., Ana Cruz Cruz; Morillo C., Yacenia; Tovar L., Yeily Paola (Revista de Ciencias Agrícolas, 2016)
The cubio (Tropaeolum tuberosum Ruíz and Pavón) is a basic tuber in the diet of Andean communities. It is a rustic crop, with medicinal uses. Farmers in the highlands of Boyacá department conserve tuber species such as cubios, rubas and ibias, as part of their cultural heritage; however, in recent years this germplasm has been threatened by genetic erosion due anthropogenic and environmental factors. There are not studies of molecular characterization of this germplasm in Boyacá, thus this research aims to identify the genetic diversity of eleven genotypes of cubios from Ventaquemada and San Pedro de Iguaque, using seven Random Amplified Microsatellite markers (RAMs). The similarity analysis differentiated the materials into two main groups, according to characteristics related to the tuber’s color and shape. The estimated heterozygosity values ranged between 0.25 and 0.42 for CGA and AG primers, respectively, which is low when compared to the results obtained in other tuberous species. The heterozygosity average in the population was 0.35, and together with the analysis of molecular variance and Fst show the existence of genetic variability in the cultivars evaluated, which should be considered in conservation programs and plant breeding of Andean tubers.